Pengaruh Penggunaan Teknologi dan Minat Belajar terhadap Prestasi Mahasiswa di Prodi Pendidikan Administrasi Perkantoran Universitas Sebelas Maret - Aldy Nugroho (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
The purpose of this study was to: 1) Whether or not there is an influence of the use of technology on student achievement in the PAP Study Program of FKIP UNS; 2) Whether or not there is an influence of interest in learning on student achievement in the PAP Study Program of FKIP UNS; and 3) Whether or not there is an influence of the use of technology and interest in learning on student achievement in the PAP Study Program of FKIP UNS. This research uses a quantitative approach with a survey method. The population in this study were active students in the PAP Study Program of FKIP UNS Class of 2019, 2020, and 2021 with the number of samples determined by the Issac and Michael table obtained 150 samples. The data analysis in this study used multiple linear regression analysis techniques with the help of the IBM SPSS 24.0 program. The results showed that: 1) There is a negative and significant effect of technology use on student learning achievement in the PAP Study Program at FKIP UNS. This is evidenced by the tcount value greater than the ttable (2.453> 1.976) and a significance value of 0.015 <0.05. 2) There is a positive and significant effect of interest in learning on student achievement in the PAP Study Program at FKIP UNS. This is evidenced by the tcount value greater than the ttable (10.905> 1.976) and a significance value of 0.000 <0.05. 3) There is a positive and significant effect of the use of technology and interest in learning simultaneously on student achievement in the PAP Study Program at FKIP UNS. This is evidenced by the value of Fcount greater than Ftable (116.615 > 3.78) and a significance value of 0.000 <0.05. The results also show that the use of technology and interest in learning together can affect learning achievement by 60.8% while the other 39.2% is influenced by other variables. Therefore, the overall results of this data analysis support the existing hypothesis.